Comparative morphology of the genera with perpendicular parameres in Anomalini (Coleoptera, Scarabaeidae, Rutelinae) allows revalidation of the endemic Mexican genus Lamoana Casey, 1915 stat. rev. - Kevin Madrigal; Santiago Zaragoza-Caballero; Andrés Ramírez-Ponce (European Journal of Taxonomy, 2023)
The endemic Mexican genus Lamoana Casey, 1915 stat. rev. is revalidated through a comparative morphological analysis of both male genitalia and somatic characters of all genera with perpendicular parameres. A comparative study and general description of the basic patterns in the morphology of the genitalia for the American genera are provided. A full redescription of the genus and a redescription of L. villosella (Blanchard, 1851) comb. rev. is provided herein, with the addition of generic and specific diagnostic characters and data about its geographical distribution. Further, possible relationships at generic level among American genera are provided. With this study, the number of Anomalini genera known for America and Mexico is now elevated to 17 and 14, respectively.